Developing State Space Models for Power Tapping and Injection in Capacitor-Coupled Substations within Transmission Networks - Nene, Sinqobile Wiseman (Current Approaches in Engineering Research and Technology Vol. 9, 2024)
The Capacitor Coupled Substation (CCS) is an emerging technology designed to tap electrical power from high-voltage (HV) transmission lines and convert it to distribution-level voltage using coupling capacitors. CCS has gained attention due to its potential for cost-effective power supply, especially in sparsely populated areas. A notable feature of CCS is its ability to perform both power tapping and power injection, with applications such as feeding microgrid-generated electricity back into the main transmission network. This dual functionality has motivated numerous studies, focusing on its integration into transmission networks and its impact on stability, including multiple CCS units operating in tandem. With its ability to control voltage stability through capacitive reactive power, CCS technology is seen as a feasible option for rural electrification. This paper develops a state-space mathematical model for the CCS system under power tapping and power injection conditions, providing a framework for analyzing such systems’ behavior and performance, particularly in rural electrification scenarios and renewable energy or microgrids integration. The use of state-space formulation simplifies the complexity of multiple variables inherent in CCS systems, offering a streamlined method for effective control and design of CCS operations.